2017
DOI: 10.1103/physrevb.96.085421
|View full text |Cite
|
Sign up to set email alerts
|

Quantum interference in coherent tunneling through branched molecular junctions containing ferrocene centers

Abstract: In our theoretical study where we combine a nonequilibrium Green's function (NEGF) approach with density functional theory (DFT) we investigate branched compounds containing ferrocene moieties in both branches which due to their metal centers are designed to allow for asymmetry induced by local charging. In these compounds the ferrocene moieties are connected to pyridyl anchor groups either directly or via acetylenic spacers in a meta-connection where we also compare our results with those obtained for the res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Usually, QI in singlemolecule junctions describes [12][13][14][15] the interference between the different molecular orbitals in the molecule. In addition, topology-broadly achieved by building parallel molecular channels into a single-molecule structure connected by covalent bonds-can also affect 5,[16][17][18][19][20][21] (Figure 1A) the conductance of the molecular junctions. In the latter case, the superposition law provides 3 a total conductance (G tot ) expressed as…”
Section: Introductionmentioning
confidence: 99%
“…Usually, QI in singlemolecule junctions describes [12][13][14][15] the interference between the different molecular orbitals in the molecule. In addition, topology-broadly achieved by building parallel molecular channels into a single-molecule structure connected by covalent bonds-can also affect 5,[16][17][18][19][20][21] (Figure 1A) the conductance of the molecular junctions. In the latter case, the superposition law provides 3 a total conductance (G tot ) expressed as…”
Section: Introductionmentioning
confidence: 99%
“…The latest studies have been carried out on a few two-terminal circuits consisting of separated molecular fragments as transport pathways, as well as a few multi-terminal circuits with the equivalent substituent positions. [27,34,35,38,40] It is reasonable to expect that more complicated QI effects could take place in multi-terminal molecular circuits. When there are multiple terminal anchors involved in a molecular circuit, a large part of the molecular fragment is shared by different transport channels, hence, strong interference interactions and other novel interesting phenomena may take place.…”
Section: G G G Gg = + +mentioning
confidence: 99%
“…For the molecules in Ref. 22 we found that the throughspace coupling between the two anchor groups is the decisive parameter causing DQI effects in the interesting energy region, i.e. in the gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) and close to the Fermi level E F .…”
Section: A Introductionmentioning
confidence: 95%
“…Experimentally, the design and synthesis of branched compounds containing ferrocene moieties in each branch has been proposed 19 for the purpose of creating single molecule junctions, where the combination of quantum interference effects with redox gating for coherent electron tunneling as well as the electrostatic correlation between spatially distinct redox centers for electron hopping 20 can be explored. A detailed theoretical analysis of branched compounds containing ferrocene centers has been published in our previous work 22 . In order to assess the generality of this analysis we apply the same models and methods to cyclic Me 2 (P(CH 3 ) 2 ) 8 (C 2 H 4 ) 4 (C 6 H 4 ) 4 bis(pyridyl-diacetylide) molecules (Fig.…”
Section: A Introductionmentioning
confidence: 99%